The role of line probe assays in the Xpert MTB/RIF Ultra era - Van Rie, Annelies; De Vos, Margaretha (Journal of Laboratory and Precision Medicine, 2017)
Tuberculosis (TB) remains an important public health problem with an estimated 10.4 million new cases diagnosed in 2015 (1). Of these, approximately 4.3 million cases went undiagnosed or unreported, posing a major hurdle to the eradication of TB (1). The control of TB is further threatened by the HIV epidemic and the emergence and spread of multidrug-resistant (MDR) TB, defined as resistance to rifampicin and isoniazid. In 2015, there were an estimated 480,000 new cases of MDR-TB and an additional 100,000 people were diagnosed with rifampicin-resistant TB. These cases result in continued transmission in communities and health care settings due to the detection and treatment gap, with only 1 million cases (30% of the 3.4 million bacteriologically confirmed cases or 10% of all cases globally) having had a drug susceptibility test for rifampicin in 2015. The WHO has therefore included early diagnosis of TB and universal drug susceptibility testing as one of its core priorities for global TB control (2).